Efeitos ecotoxicológicos de herbicida e de inseticida biológico em solo: estudo com minhocas Eisenia andrei - Gadini, Rafael Schroeder (2024)
The use of herbicides combined with insecticides is motivated by the need to control weeds and pests that occur concurrently in agricultural crops. Even with the increasing use of these products to ensure productivity, there is a concern directed towards the toxicity caused in non-target organisms, risks to human health, and effects on the environment. Therefore, this study aims to assess the ecotoxicity of the herbicide 2,4-D + Picloram® and the biological insecticide based on Bacillus thuringiensis in soil, using the earthworm Eisenia andrei as a bioindicator. The tests were carried out during 28 days of exposure and evaluated the interaction between the compounds and the assessment of biomarkers of antioxidant activity (ACAP, CAT, GPx, and GR), oxidative stress (Peroxide, ROS, Carbonyl, NO, TBARS), and neurotoxicity (AChE and BChE) in earthworms exposed to the following treatments: CT- control; CD- 2,4-D and Picloram® (4L/ha); BT- Bacillus thuringiensis; and CDB- 2,4-D and Picloram® (4L/ha) + Bacillus thuringiensis (1L/ha). After 14 and 28 days of exposure, the results revealed that the CDB treatment induced oxidative stress, evidenced by the high levels of reactive oxygen species (ROS) and a reduction in the activity of the catalase (CAT) enzyme. Although there was a compensatory response of the antioxidant system, with an increase in glutathione reductase (GR), prolonged exposure appears to have exceeded the adaptive capacity of the earthworms. Additionally, the CDB treatment also showed neurotoxic effects, with an increase in acetylcholinesterase (AChE) activity and a reduction in butyrylcholinesterase (BChE), indicating changes in the nervous system of the earthworms. Overall, the mixture of herbicides with the biological insecticide proved to be more harmful to non-target organisms than when applied individually, suggesting the need for a more comprehensive assessment of the effects of combined compounds in the soil and their potential ecological risks.